2014
DOI: 10.18438/b8r88c
|View full text |Cite
|
Sign up to set email alerts
|

The Scholarly Communications Needs of Faculty: An Evidence-Based Foundation for the Development of Library Services

Abstract: the terms of the Creative Commons-AttributionNoncommercial-Share Alike License 4.0 International (http://creativecommons.org/licenses/by-nc-sa/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. AbstractObjectives -This exploratory research seeks to broadly understand the publishing behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…These results clarify the findings of other studies that have found knowledge gaps and uncertainty in the health sciences regarding open access and scholarly communication, including those by: Spezi (2013), Charbonneau and McGlone (2013), Cullen andChawner (2011), Creaser et al (2010), Dawson (2014) , andFry et al (2009). The results reported here reveal significant disciplinary differences with regard to specific aspects and elements of the scholarly communication environment.…”
Section: A Knowledge Gap In the Health Sciencessupporting
confidence: 88%
“…These results clarify the findings of other studies that have found knowledge gaps and uncertainty in the health sciences regarding open access and scholarly communication, including those by: Spezi (2013), Charbonneau and McGlone (2013), Cullen andChawner (2011), Creaser et al (2010), Dawson (2014) , andFry et al (2009). The results reported here reveal significant disciplinary differences with regard to specific aspects and elements of the scholarly communication environment.…”
Section: A Knowledge Gap In the Health Sciencessupporting
confidence: 88%
“…Open Access publishing, including Dawson, 2014 andMcDonald, Gibson, Yates, &Stephenson, 2016), academic librarians continue to grapple with how best to support faculty with the interpretation, location, and appropriate use of types of metrics. Research has described approaches that academic librarians can and do use to address the bibliometric needs of faculty (Corrall, Kennan, & Afzal, 2013;Hendrix, 2010;Suiter & Moulaison, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moore (2011) and Dawson (2014) furthermore noted a high degree of support for the principle of OA among their respective respondents. However, the studies reviewed also demonstrated a wide range of faculty participation in OA journal publishing, from a low of 33% to a high of 71% (Fowler, 2011, Table 7;Wiley, 2012;Dallmeier-Tiessen et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Canadian studies at the University of Toronto, University of Saskatchewan, and York University found that faculty had considerable awareness of OA (Moore, 2011;Dawson, 2014;Nariani & Fernandez, 2012). Moore (2011) and Dawson (2014) furthermore noted a high degree of support for the principle of OA among their respective respondents.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation